Aberrant Splicing Is the Pathogenicity Mechanism of the p.Glu314Lys Variant in CYP11A1 Gene - Goursaud, Claire; Mallet, Delphine; Janin, Alexandre; Menassa, Rita; Tardy-Guidollet, Véronique; Russo, Gianni; Lienhardt-Roussie, Anne; Lecointre, Claudine; Plotton, Ingrid; Morel, Yves; Roucher-Boulez, Florence (Frontiers in Endocrinology, 2018)
Context: The cholesterol side chain cleavage enzyme (CYP11A1) catalyzes the conversion of cholesterol to pregnenolone, the first rate-limiting step of steroidogenesis. CYP11A1 mutations are associated with primary adrenal insufficiency (PAI) as well as disorders of sex development (DSD) in 46,XY patients. Objective: To define the pathogenicity mechanism for the p.Glu314Lys variant, previously reported, and found in four additional patients with CYP11A1 deficiency. Subjects and Methods: DNA of four patients presenting with delayed PAI and/or 46,XY DSD were studied by Sanger or Massively Parallel sequencing. Three CYP11A1 mutations were characterized in vitro and in silico, and one by mRNA analysis on testicular tissue. Results: All patients were compound heterozygous for the previously described p.Glu314Lys variant. In silico studies predicted this mutation as benign with no effect on splicing but mRNA analysis found that it led to incomplete exon 5 skipping. This mechanism was confirmed by minigene experiment. The protein carrying this mutation without exon skipping should conserve almost normal activity, according to in vitro studies. Two other mutations found in trans, the p.Arg120Gln and p.Arg465Trp, had similar activity compared to negative control, consistent with the in silico studies. Conclusions: We provide biological proof that the p.Glu314Lys variant is pathogenic due to its impact on splicing and seems responsible for the moderate phenotype of the four patients reported herein. The present study highlights the importance of considering the potential effect of a missense variant on splicing when it is not predicted to be disease causing.